2017
DOI: 10.7326/m17-0212
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sedentary Behavior and Mortality in U.S. Middle-Aged and Older Adults

Abstract: Background Excessive sedentary time is ubiquitous in Westernized societies. Previous studies have relied on self-report to evaluate the total volume of sedentary time as a prognostic risk factor for mortality and have not examined whether the manner in which sedentary time is accrued (in short or long bouts) carries prognostic relevance. Objective To examine the association of objectively-measured sedentary behavior (its total volume and accrual in prolonged, uninterrupted bouts) with all-cause mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
367
8
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 421 publications
(404 citation statements)
references
References 38 publications
23
367
8
6
Order By: Relevance
“…22 Additionally, a recent study of older women found that the raised risks of mortality associated with higher sedentary time were fully attenuated after adjusting for MVPA. 27 In our study, each 30 min/day increase in LIPA was associated with a 17% reduction in mortality, which was robust to adjustment for sedentary behaviour and MVPA, suggesting that the increase in LIPA rather than the reduction in sedentary behaviour was most important. In a younger NHANES sample, a reduction in mortality of 16% was found per hour of LIPA.…”
Section: Pa Intensity and Durationsupporting
confidence: 54%
See 2 more Smart Citations
“…22 Additionally, a recent study of older women found that the raised risks of mortality associated with higher sedentary time were fully attenuated after adjusting for MVPA. 27 In our study, each 30 min/day increase in LIPA was associated with a 17% reduction in mortality, which was robust to adjustment for sedentary behaviour and MVPA, suggesting that the increase in LIPA rather than the reduction in sedentary behaviour was most important. In a younger NHANES sample, a reduction in mortality of 16% was found per hour of LIPA.…”
Section: Pa Intensity and Durationsupporting
confidence: 54%
“…Data are from a population-based cohort of community-dwelling older predominantly white British men, so results may not apply to women, other ethnicities or younger men; however, other studies have not found evidence that the associations between PA or sedentary behaviour and mortality differ by gender 17 23 25 26 36 and a recent study of older women finds associations in the same direction as ours, although due to methodological differences it is hard to compare effect sizes. 27 Given that LIPA and sedentary time are highly correlated, it can be difficult to distinguish their effects; we did not use isotemporal substitution analyses as the sedentary behaviour and LIPA were too highly correlated, resulting in problems with collinearity and model convergence. In sensitivity analyses, our findings did not meaningfully change after exclusion of men with mobility disability, prevalent CVD and the first year of follow-up, suggesting findings are not likely to be due to reverse causality.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with data from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study from the United States, in which middle-aged and older adults spend 77.4% of their time in sedentary behaviours. 40 Other studies found similar results. 39 By contrast, older Norwegians have a more active lifestyle, when compared with the Portuguese population.…”
Section: Health Characteristicsmentioning
confidence: 56%
“…Long periods of sedentary activity are common among older adults and have a negative impact on both physical and mental health (Diaz et al, 2017; Dunstan, Thorp, & Healy, 2011; Hamer & Stamatakis, 2014). This is true even for those who meet the guidelines for time spent in moderate level activity.…”
Section: Discussionmentioning
confidence: 99%